Can the comet assay be used reliably to detect nanoparticle‐induced genotoxicity?. (8th December 2014) - Karlsson, Hanna L.; Di Bucchianico, Sebastiano; Collins, Andrew R.; Dusinska, Maria
<x xml:space="preserve">Abstract</x> The comet assay is a sensitive method to detect DNA strand breaks as well as oxidatively damaged DNA at the level of single cells. Today the assay is commonly used in nano‐genotoxicology. In this review we critically discuss possible interactions between nanoparticles (NPs) and the comet assay. Concerns for such interactions have arisen from the occasional observation of NPs in the "comet head", which implies that NPs may be present while the assay is being performed. This could give rise to false positive or false negative results, depending on the type of comet assay endpoint and NP. For most NPs, an interaction that substantially impacts the comet assay results is unlikely. For photocatalytically active NPs such as TiO2, on the other hand, exposure to light containing UV can lead to increased DNA damage. Samples should therefore not be exposed to such light. By comparing studies in which both the comet assay and the micronucleus assay have been used, a good consistency between the assays was found in general (69%); consistency was even higher when excluding studies on TiO2 NPs (81%). The strong consistency between the comet and micronucleus assays for a range of different NPs—even though the two tests measure different endpoints—implies that both can be trusted in assessing the genotoxicity of NPs, and that both could be useful in a standard battery of test methods. Environ. Mol. Mutagen. 56:82–96, 2015. © 2014 Wiley Periodicals, Inc.